Efficient modification of Si/SiOx nanoparticles by pulse-modulated plasma flash evaporation for an improved capacity of lithium-ion storage. (7th June 2019) - Kambara, M; Hamazaki, S; Kodama, N; Tanaka, Y
Abstract: Composite Si/SiO z nanoparticles have been produced from SiO powder feedstock by pulse-modulated plasma flash evaporation (PFE) and the effect on the lithium-ion battery properties are analyzed. With the introduction of power and powder-feeding pulse-modulation during PFE, the primary SiO x particle size decreases from 27.9 to 14.3 nm and the core crystalline Si is reduced from 14.2 to 7.3 nm. Although no appreciable reduction in the overall oxygen content ( x ) in the SiO x representation is confirmed, the composite nanoparticles with amorphous Si core are formed by the modulation due to the disproportionation reaction at lower temperatures. As a result, the coulombic efficiency is improved, and the higher cycle capacities are attained for the battery using the modulated nanoparticles as an anode.